Assessment of genetic variability and resistance against stem and root rot caused by Macrophomina phaseolina in segregating generations of sesame (Sesamum indicum L.): ASSESSMENT OF GENETIC VARIABILITY AND RESISTANCE AGAINST STEM AND ROOT ROT OF SESAME - M JAYARAMACHANDRAN; V RAVICHANDRAN; R VAITHIYALINGAN (Journal of Oilseeds Research, 2021)
An investigation was carried out to assess the genetic variability and disease resistance against stem and root rot caused by Macrophomina phaseolina in sesame. Segregating generations of ten cross combinations involving the sesame varieties viz., VRI 1, TMV 3, TMV 4, TMV 6 as female parents and ORM 7, ORM 14, ORM 17 as male parents were used. The genetic variability parameters viz., GCV (%), PCV (%), heritability (h2) and Genetic Advance (GA) were estimated in F2 generation for the traits plant height, number of primary branches/plant, number of capsules/plant, number of leaves/plant, capsule leaf ratio and single plant yield. High GCV(%) and PCV (%) were recorded for the traits number of primary branches/panicle, number of capsules/plant and number of leaves/plant in F2s of all the ten cross combinations revealed the presence of enough genetic variability for these traits. High heritability coupled with high genetic advance were recorded for the traits viz., plant height, number of primary branches/plant, number of capsules/plant, number of leaves/plant and single plant yield unveiled that these traits are governed by additive gene action. Hence, hybridization followed by simple recurrent selection based on the progeny testing could be useful for improving these traits. Disease reaction studies of F3 generation in sick plot concluded that three crosses viz., Cross IV (TMV 3 X ORM 7), Cross VII (TMV 4 X ORM 7) and Cross X (TMV 6 X ORM 7) are moderately resistant for stem and root rot disease and Cross IV (TMV 3 X ORM 7) recorded highest mean single plant yield of 15.6 g/plant. Hence, Cross IV (TMV 3 X ORM 7) may be utilised for improving the yield and root rot resistance in sesame.